AN EMERGENT APPROACH TO PUBLIC PROCUREMENT - Fletcher, Jo (The journal of contemporary issues in business and government, 2006)
This paper considers the design of a dynamic measurement framework for public procurement from an emergent system’s perspective. In order to continue into sustainable excellence, an adaptable and reliable measurement system is needed to measure procurement’s current performance and make well-informed sustainable decisions into the future in the context of a changing political environment. Measurements would need to include: public confidence (with ethical accountability and transparency), efficiency and effectiveness (as measured in value for money and the delivery of procurement outcomes) and policy compliance and consistency. These measures would need to be nested in a larger measurement system (as reflected in a sustainable generic public management system that would reflect quality of life as opposed to simply material wealth). In terms of design principals for such a measurement system, three main themes have emerged in the literature. First, organisations are complex multidimensional nested systems, second the integrity of the whole system needs to be maintained and third, in order to improve complex social systems, such as large public procurement entities, performance management systems need to function as an ethical learning tool. The actual design of an integrated measurement system to gauge procurement performance within public procurement is potentially a research area for the future.